The one-ski-method—effects of an alternative teaching approach on selected movement patterns in alpine skiing - Kurpiers, Nicolas (Cogent social sciences, 2017)
Teaching methods in skiing have marginally developed within the last decades. An intervention comparing the conventional approach (SP) and the One-Ski-Method (OSM) is proposed in which the main body actions are first trained on one ski and successively transferred to two skis. The OSM teaches the main body actions towards a proper position on parallel skis. The snowplow gets avoided as it implies obstructive body actions. Two groups were trained using each method. Video footage from the first and the fifth day were evaluated by experts following selected criteria. OSM learners showed significantly larger improvements compared to SP. Results indicate a faster acquisition of key elements of alpine skiing and provide a foundation for further investigations of the OSM method.